Hepatitis C Screening as a Sentinel of Unsafe Healthcare in Humanitarian and Low-resource Settings - Francesco De Maria; Ludovico Abenavoli; Francesco Branda; Giancarlo Ceccarelli; Massimo Ciccozzi; Alessandro Russo (The International Journal of Gastroenterology and Hepatology Diseases, 2026)
Hepatitis C virus (HCV) infection remains a major global health challenge despite the availability of highly effective direct-acting antivirals. In humanitarian and resource-constrained settings, however, HCV epidemiology may provide insights extending beyond the burden of chronic liver disease itself. A narrative review of published literature and public health reports was conducted, using searches of PubMed and Google Scholar up to May 2026, focusing on HCV epidemiology, healthcare-associated transmission, and infection prevention challenges in displaced populations. Particular attention was given to evidence from Rohingya refugee camps in Cox’s Bazar, Bangladesh, where recent studies have reported HCV seroprevalence approaching 30% and active infection rates close to 20%. Emerging data suggest that healthcare-related exposures, including medical injections and surgical procedures, may contribute to transmission in this setting. Nevertheless, direct evidence of unsafe healthcare practices remains limited, and alternative explanations, including historical exposures, informal healthcare pathways, and traditional blood-related practices, should also be considered. It was proposed that unexpectedly high HCV prevalence in populations without clearly documented behavioral risk factors may function as a sentinel epidemiological signal warranting further assessment of healthcare safety and healthcare-associated transmission pathways. In this context, screening programmes may provide information not only for case finding and treatment initiation but also for identifying potential weaknesses in infection prevention and control systems. While test-and-treat strategies remain essential, sustainable progress toward HCV elimination in humanitarian settings will likely require parallel investments in safer healthcare delivery and strengthened infection prevention measures.